Design Out Crime: Creating Safe and Sustainable Communities - Marome, Wijitbusaba Ann (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Crime and fear of crime are significant concerns for communities, including residents, workers and so on. There are many driving factors, including social exclusion, poverty, drug abuse, psychological problems, family breakdown, economic trends and so on, behind crime. Inferior grade of designs of housing and residential environment are also one of the key driving factors of crime and fear of crime.